1991
DOI: 10.1017/s0308229600019681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active immunization against inhibin and androstenedione, separately or together, on hormone profiles, ovarian follicle populations and ovulation rate in heifers

Abstract: It was postulated that the induction of twin ovulations in cattle may require a combination of two appropriate stimuli. The first putative requirement is an increase in the circulating FSH concentrations and/or a decrease in inhibin concentrations to induce the development of additional potentially ovulatory follicles. The second putative requirement is an increase in LH pulse frequency during the follicular phase of the cycle to enhance the stimulus for follicle maturation and ovulation. On the basis of studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, despite some recent preliminary evidence to the contrary (Scanlon, Boland, Ireland & Martin, 1990;Rhind, Schemm & Schanbacher, 1991) the pre¬ sent data clearly show that active immunization against a synthetic fragment of inhibin can promote multiple follicular development and raise ovulation rate in heifers. The reason for the discrepancies between different studies in cattle remains obscure al¬ though the use of different inhibin-peptide conjugates may explain some of the variation in response.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, despite some recent preliminary evidence to the contrary (Scanlon, Boland, Ireland & Martin, 1990;Rhind, Schemm & Schanbacher, 1991) the pre¬ sent data clearly show that active immunization against a synthetic fragment of inhibin can promote multiple follicular development and raise ovulation rate in heifers. The reason for the discrepancies between different studies in cattle remains obscure al¬ though the use of different inhibin-peptide conjugates may explain some of the variation in response.…”
Section: Discussionmentioning
confidence: 85%
“…(1990) nor Rhind et al (1991) confirmed that their peptide-immunized heifers produced antibodies which bound native inhibin. Further preliminary reports of increased follicular development and ovulation rate in inhibin-immunized beef heifers have recently appeared (Sunderland, Goulding, Kane et al 1991;Morris, McDermott & Sreenan, 1991) which support the findings of the present study.…”
Section: Discussionmentioning
confidence: 90%